Variables Impacting Post-Retinal Detachment Visual Outcomes - Asna Tahir, Syed Shujaat Ali Shah, Nesr Farooq, Muhammad Naeem, Muhammad Awais Ashraf, Lt Col Ayyaz Hussain Awan, Bilal Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The purpose of this study was to determine how often patients whose retinal detachment symptoms did not improve after surgery and how often treatment was successful in terms of visual and surgical results. Methods: This quasi experiment was conducted at Department of Ophthalmology Khyber Teaching Hospital Peshawar. In this study 60 patients with 60 eyes were included. We evaluated all cases of delayed retinal detachment that underwent Pars Plana Vitrectomy (PPV) and followed them up for 6 months. We looked at the anatomical attachment of the retina, pre- and post-surgery Best Corrected Visual Acuity (BCVA), and factors that affect anatomical success. SPSS 22.0 was used to analyze all data. Results: There were 38 (63.3%) males and 22 (36.7%) females among all cases. The patients average age was 45.16 years. Post-operative significant improvement was seen in visual acuity <0.004. The multiple logistic regression analysis found that three factors—primary anatomic success (p=0.047), preoperative visual acuity (6/60 or better; p=0.025), and lack of advanced PVR grade C-1 or worse (p=0.010)—had a positive effect on visual outcome. Conclusion: Preoperative visual acuity of 6/60 or greater, absence of posterior vitreous reattachment grade C-1 or worse, and primary anatomic success all contribute to a good visual prognosis following surgery for rhegmatogenous retinal detachment. Keywords: optical coherence tomography, rhegmatogenous retinal detachment